Expert consensus on the clinical application of high‐frequency electrosurgery in digestive endoscopy (2020, Shanghai). Issue 1 (27th January 2022) - Bai, Yu; Yang, Fan; Liu, Cui; Li, De Feng; Wang, Shi; Lin, Rong; Ding, Zhen; Meng, Wen Bo; Li, Zhao Shen; Linghu, En Qiang; ,; ,; et al.
Abstract : High‐frequency electrosurgery has been widely applied in digestive endoscopy with constantly expanding indications. However, high‐frequency electrosurgery may cause possible complications such as hemorrhage or perforation during or after the procedure, of which endoscopists must be cautious. Digestive endoscopists must have a firm grasp of the principles of high‐frequency electrosurgery as well as its safety issues so as to improve the safety of its clinical application. To this end, experts in gastroenterology and hepatology, digestive endoscopy, surgery, nursing and other related fields were invited to draft a consensus on the clinical application of high‐frequency electrosurgery in digestive endoscopy based on relevant domestic and international literatures and their experiences.